Land subsidence prediction in central plain of Thailand - Piyakarn Teartisup (2015)
The aim of this research was to analyze risk areas of land subsidence. Risk factors were selected from related research on the problem of land subsidence. There were six factors selected: geological, hydrogeological, number of wells, groundwater used, land use and amount of population. The factors were analyzed by weighting and rating scores from twelve governmental officers from concerned agencies. The total score of each factor was employed to assess risk area of land subsidence by GIS and PCA method. The output in this study is a map of risk area of land subsidence in Nakhon Pathom Province, representative central plain area. In this study, the risk area of land subsidence was classified into 3 levels. Most of the land consisted of areas at a moderate risk of subsidence and these areas were scattered throughout the study area, covering 1,905.93 km2, while a high level to at risk areas was found in parts of the west and south of the study area, covering 251.02 km2. The low level of land subsidence risk covered the least area, at only 14 km2, mainly in the northwestern and eastern parts of the study area. Furthermore, the results showed land subsidence is most heavily influenced by excessive utilization of groundwater. The second most influential factor is the number of wells. A comparison of bench marks from the Royal Thai Survey Department, ground checks of the real situation and the assessments made in this study showed all.